Paratekst w badaniach lingwistycznych (rekonesans badawczy) = Paratext in linguistic research (research reconnaissance) - Uździcka, Marzanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The considerations undertaken in the article result from a research project carried out in recent years on the issue of the functioning of paratexts in popular culture texts. The first part characterizes the concept of paratext as seen by its creator, French literary scholar Gérard Genette, and the reception process of his ideas in Polish linguistic research to date.
Keywords: paratekst; paratektualność; metatekst; tekst; Genette, Gérard (1930-2018); paratext; paratextuality; metatext; text